Comportamento de acasalamento e atratividade ao ferômonio sexual de Gyropsylla spegazziniana Lizer & Trelles (HEMIPTERA: PSYLLIDAE) - Walerius, Adriana Helena (2017)
Gyropsylla spegazziniana (Hemiptera: Psyllidae) is considered an important pest of the yerba mate (Ilex paraguariensis), causing considerable economic losses. Most insects use chemical, visual, or acoustic signals in interspecific communication. Sex pheromones are the main signals involved in mating behavior. In this sense, this work aimed to describe the mating behavior of G. spegazziniana, to verify the attractiveness between males and females in Y olfactometer bioassays, and to identify the sex pheromone of this species. To describe the mating behavior virgin couples were placed in cages containing a yerba mate seedling. The insect behavior during the photophase and scotophase was observed. For behavioral tests in Y-olfactometer, virgin males or virgin females and a branch of yerba mate were used as odor source. To verify the presence of a sexual pheromone, body extracts of virgin males or virgin females were obtained and were analyzed by using gas chromatograph coupled to mass spectrometer (GC-MS). Mating occurred only during the photophase, in the scotophase the couples remained immobile in the abaxial surface of the leaves. The mating sequence showed that the female walks on the new leaves and the male goes to meet her, standing face to face with her. After a brief antennal touch between the couple, the male turns the abdomen and attaches to the female. As a result of Y olfactometer bioassays, males and females were attracted to females in the olfactometer but were not attracted to males, suggesting a presence of volatiles released by females for sexual attraction. There was a presence of a single female-specific compound, identified as 2-nonadecanone, that may act as sex pheromone.The results suggest that G. spegazziniana females release sex pheromone to attract males for mating. The compounds released by the females can interact with the volatiles emitted by the yerba mate, resulting in the attractiveness of G. spegazziniana males.